Global religions and international relations: a diplomatic perspective - Ferrara, Pasquale (Palgrave Studies in Religion, Politics, and Policy, 2014)
Introduction 1. - Part I: A Theoretical Overview. - 1. Religion and world politics 25. - 2. Religions and global governance 41. - Part II: Issues and Applications . - 3. Islam between national and international politics 53 . - 4. The Catholic Church and the global shift of power 92. - 5. Religious Freedom in the international practice 104